(METH) acrylic resin film, adhesive sheet, and polarizing film
A (meth)acrylic resin composition with specific polymers and additives is used to form thin films with improved solvent resistance and adhesion, addressing the limitations of existing PMMA resin film production methods.
Patent Information
- Application Number
- JP2023106064
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-17
AI Technical Summary
Existing methods for producing PMMA resin films face challenges in achieving thin film thicknesses of 40 μm or less and improving solvent resistance, while maintaining optical properties, especially in solution casting methods where high viscosity and low workability hinder film formation.
A (meth)acrylic resin composition is developed, comprising specific polymers, crosslinking agents, antioxidants, and rubber compounds, which are crosslinked to form thin layers with improved solvent resistance and adhesion, using a solution casting method.
The composition results in (meth)acrylic resin films with excellent fold resistance, cut resistance, elongation, and solvent resistance, enhancing adhesion to adherends while maintaining optical properties.
Smart Images

Figure 2025005743000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a (meth)acrylic resin film, a pressure-sensitive adhesive sheet, and a polarizing film. [Background technology]
[0002] Traditionally, (meth)acrylic resins (PMMA resins) have been used in resin films for surface coating of various equipment parts such as electronic devices, home appliances, automobile interior / exterior parts, and building materials, due to their excellent transparency, heat processability, weather resistance, and chemical resistance. In recent years, PMMA resin films have also been used as optical films due to their excellent transparency and weather resistance. Traditionally, the method of producing PMMA resin films has been the melt extrusion method, which is highly productive.
[0003] For example, Patent Document 1 discloses an acrylic resin film that can be used as an alternative to paint and is suitable for use in components that are integrated with molded resins, particularly for forming a protective layer on the surface. In Patent Document 1, specific types of ultraviolet absorbents and lubricants are added to the acrylic resin film in a specific ratio.
[0004] Patent Document 2 discloses a method for improving the impact resistance of an acrylic resin without including a rubber-containing graft copolymer, which causes a loss in color tone and transparency of the acrylic resin. In Patent Document 2, an acrylic resin composition containing a specific graft copolymer is used. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-286960 A [Patent Document 2] International Publication No. 2016 / 139927 Summary of the Invention [Problem to be solved by the invention]
[0006] The acrylic resin film according to the invention described in Patent Document 1 is a resin film produced by melt extrusion, and therefore has a problem in that it is difficult to obtain a thin resin film having a thickness of 40 μm or less. The acrylic resin composition according to the invention described in Patent Document 2 is produced by gradually carrying out graft polymerization reactions in three to four stages to complete a graft copolymer, and therefore has a problem in that the process of obtaining the graft copolymer takes a long time.
[0007] In this situation, there was a demand for a method of forming PMMA resin films using the solution casting method, which is a simpler resin film formation method compared to the melt extrusion method and has the advantage of being able to form thin films. Furthermore, the demand for thinner films is increasing day by day for optical and display applications in which PMMA resin is used, and this is reaching an area where film formation using the melt extrusion method is not possible.
[0008] On the other hand, when a PMMA resin film is produced by the solution casting method, it is possible to reduce the thickness to 40 μm or less, but there is a problem that it is difficult to improve the solvent resistance performance as a physical property of the obtained PMMA resin film. In the solution casting method, the weight average molecular weight of the uncrosslinked PMMA resin used in the PMMA resin composition needs to be a large value of 1 million or more, so the solution of the PMMA resin composition has a high viscosity, and there is a problem that the workability in the film production process is low.
[0009] The present invention aims to provide a (meth)acrylic resin film, a pressure-sensitive adhesive sheet, and a polarizing film that have improved adhesion to an adherend while maintaining optical properties, by using a (meth)acrylic resin composition that has excellent folding resistance, cut resistance, elongation, and solvent resistance. [Means for solving the problem]
[0010] A first aspect of the present invention is a (meth)acrylic resin film comprising a first resin layer formed by crosslinking a first (meth)acrylic resin composition containing (A) a first (meth)acrylic polymer, a rubber compound, (A-3) a first crosslinking agent, and (A-4) a first antioxidant, and a second resin layer formed by crosslinking a second (meth)acrylic resin composition containing (B) a second (meth)acrylic polymer, (B-3) a second crosslinking agent, and (B-4) a second antioxidant, the second resin layer being an adhesion improving resin layer for the first resin layer, the (A) first (meth)acrylic polymer being (A-1) a first alkyl (meth)acrylate, The copolymer has a weight average molecular weight of more than 100,000 and not more than 1,000,000, and is obtained by copolymerizing 80 parts by weight or more of methyl methacrylate, 100 parts by weight of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or higher and the alkyl group has a carbon number of C1 to C14, and 1.0 to 20.0 parts by weight of at least one copolymerizable monomer having a functional group capable of reacting with the first crosslinking agent (A-3), and the rubber compound is present in an amount of 1.0 to 25.0 parts by weight, and the (B) second (meth)acrylic polymer is composed of (B-1) a second alkyl (meth)acrylate, which is composed of 80 parts by weight or more of methyl methacrylate and 100 parts by weight of a total of at least one alkyl (meth)acrylate other than the methyl methacrylate, which has a homopolymer Tg of 0° C. or less and has an alkyl group having a carbon number of C2 to C18, and (B-2) a second copolymerizable monomer, which does not contain a carboxyl group and contains a hydroxyl group, and The (B-1) second crosslinking agent is a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, copolymerized with at least one of 5 to 30 parts by weight in total, the (B-3) second crosslinking agent is a bifunctional or higher isocyanate compound, the (B-3) second crosslinking agent is in a ratio of 1 to 5 parts by weight per 100 parts by weight in total of the (B-1) second alkyl (meth)acrylate, the thickness of the first resin layer is 10 μm or less, the thickness of the second resin layer is 5 μm or less, and the haze value of the (meth)acrylic resin film is 1.0% or less.
[0011] The second aspect is the first aspect, wherein the (A-2) first copolymerizable monomer is at least one monomer selected from the group of monomers consisting of copolymerizable monomers containing a hydroxyl group and copolymerizable monomers containing a carboxyl group, the (A-3) first crosslinking agent is at least one selected from the group of compounds consisting of epoxy compounds, aziridine compounds, and isocyanate compounds, the (A-3) first crosslinking agent is present in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the (A-1) first alkyl (meth)acrylate, and the (A-4) first antioxidant is at least one selected from the group of phenol-based antioxidants, thioether-based antioxidants, phosphite-based antioxidants, and hindered amine-based antioxidants, and the (A-4) first antioxidant is present in an amount of 0.01 to 0.5 parts by weight per 100 parts by weight of the (A-1) first alkyl (meth)acrylate.
[0012] In a third aspect, in the first or second aspect, the rubber compound is a core-shell particle formed of a rubber layer mainly made of SBR or butadiene in the core portion and an acrylic layer mainly made of methyl methacrylate in the shell portion, and the core-shell particle has a volume-based average particle diameter of 0.1 to 0.3 μm.
[0013] A fourth aspect is any one of the first to third aspects, wherein the (A-2) first copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group and is at least one selected from 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxyethyl methacrylate.
[0014] A fifth aspect is any one of the first to fourth aspects, wherein the (B-4) second antioxidant is at least one selected from a phenol-based antioxidant, a thioether-based antioxidant, a phosphite-based antioxidant, and a hindered amine-based antioxidant, and the ratio of the (B-4) second antioxidant is 0.01 to 0.5 parts by weight per 100 parts by weight in total of the (B-1) second alkyl (meth)acrylate.
[0015] A sixth aspect is any one of the first to fifth aspects, wherein the (B-2) second copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group and is at least one selected from 8-hydroxyoctyl acrylate, 6-hydroxyhexyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxyethyl acrylate.
[0016] A seventh aspect is any one of the first to sixth aspects, wherein the first resin layer has a thickness of 0.1 to 9 μm, and the second resin layer has a thickness of 0.1 to 5 μm. An eighth aspect is any one of the first to seventh aspects, wherein the (meth)acrylic resin film has an in-plane retardation Re of 1.0 nm or less. In a ninth aspect, in any one of the first to eighth aspects, the (meth)acrylic resin film has a gel fraction as a solvent resistance of 90% or more, and a folding endurance (JIS P8115) of 200 or more and a breaking elongation of 20% or more as folding endurance.
[0017] A tenth aspect is any one of the first to ninth aspects, in which, in a cellophane tape adhesion test in which the (meth)acrylic resin film is bonded to one side of a polarizer with a PVA adhesive, and then cellophane tape is bonded to a surface of the (meth)acrylic resin film and then peeled off, the (meth)acrylic resin film does not peel off and only the cellophane tape peels off.
[0018] An eleventh aspect is a pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed on one or both sides of the (meth)acrylic resin film of any one of the first to tenth aspects. A twelfth aspect is a polarizing film comprising the (meth)acrylic resin film according to any one of the first to tenth aspects formed on one or both sides of a polarizer, and having a total thickness of 80 μm or less. Effect of the Invention
[0019] According to the present invention, by using a (meth)acrylic resin composition having excellent folding resistance, cut resistance, elongation and solvent resistance, it is possible to provide a (meth)acrylic resin film, a pressure-sensitive adhesive sheet and a polarizing film having improved adhesion to an adherend while maintaining optical properties.
[0020] The first resin layer contains a first (meth)acrylic polymer made of a copolymer obtained by copolymerizing specific monomers in a specific ratio, a rubber compound, and a first antioxidant, so that a (meth)acrylic resin film having excellent folding resistance, cut resistance, elongation, and solvent resistance, especially with significantly improved folding resistance and elongation, can be obtained. The second resin layer is laminated on the first resin layer as an adhesion improving resin layer, so that the adhesion to the adherend can be improved. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of a (meth)acrylic resin film according to an embodiment. [Diagram 2] FIG. 1 is a cross-sectional view illustrating an example of a pressure-sensitive adhesive sheet according to an embodiment. [Diagram 3] FIG. 1 is a cross-sectional view illustrating an example of a polarizing film according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described below based on preferred embodiments. The (meth)acrylic resin film of the embodiment is a (meth)acrylic resin film 10 in which a first resin layer 11 and a second resin layer 12 serving as an adhesion improving resin layer for the first resin layer 11 are laminated, as shown in FIG.
[0023] The first resin layer 11 is formed by crosslinking a first (meth)acrylic resin composition containing (A) a first (meth)acrylic polymer, a rubber compound, (A-3) a first crosslinking agent, and (A-4) a first antioxidant. The second resin layer 12 is formed by crosslinking a second (meth)acrylic resin composition containing (B) a second (meth)acrylic polymer, (B-3) a second crosslinking agent, and (B-4) a second antioxidant. The first resin layer 11 has a thickness of 10 μm or less, and the second resin layer 12 has a thickness of 5 μm or less. The (meth)acrylic resin film 10 has a haze value of 1.0% or less.
[0024] In this specification, the (meth)acrylate may be either an acrylate and / or a methacrylate, or a combination of both.
[0025] <First (meth)acrylic resin composition> The first (meth)acrylic resin composition is used to form the first resin layer 11. The rubber compound contained in the first resin layer 11 is in a ratio of 1.0 to 25.0 parts by weight with respect to 100 parts by weight in total of the (A-1) first alkyl (meth)acrylate.
[0026] (A) The first (meth)acrylic polymer is a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, obtained by copolymerizing (A-1) a first alkyl (meth)acrylate, which is 80 parts by weight or more of methyl methacrylate, 100 parts by weight in total of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or higher and the alkyl group has carbon atoms of C1 to C14, and (A-2) a first copolymerizable monomer, which is 1.0 to 20.0 parts by weight in total of at least one copolymerizable monomer having a functional group capable of reacting with (A-3) a first crosslinking agent.
[0027] The (A) first (meth)acrylic polymer is a copolymer obtained by copolymerizing the (A-1) first alkyl (meth)acrylate and the (A-2) first copolymerizable monomer. The (A) first (meth)acrylic polymer may be a copolymer consisting of only the (A-1) first alkyl (meth)acrylate and the (A-2) first copolymerizable monomer, or may be a copolymer further containing other monomers.
[0028] The alkyl group of the first alkyl (meth)acrylate (A-1) may be either acyclic (straight-chain or branched) or cyclic. In the following description, 100 parts by weight of the first alkyl (meth)acrylate (A-1) in total may be referred to as "100 parts by weight of (A-1) in total."
[0029] (A-1) first alkyl (meth)acrylate contains (A-1a) methyl methacrylate in a ratio of 80 parts by weight or more out of a total of 100 parts by weight of (A-1). The ratio of (A-1a) may be within a range between any two points selected from 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, and 99 parts by weight.
[0030] The (A-1) first alkyl (meth)acrylate contains, in addition to (A-1a) methyl methacrylate, at least one kind of (A-1b) alkyl (meth)acrylate other than the (A-1a) whose homopolymer has a Tg of 0°C or higher and whose alkyl group has a carbon number of C1 to C14.
[0031] Specific examples of (A-1b) include one or more compounds selected from the group consisting of methyl acrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, s-butyl methacrylate, t-butyl (meth)acrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, cyclohexyl (meth)acrylate, and the like.
[0032] The (A-1) first alkyl (meth)acrylate contains 20 parts by weight or less of a monomer corresponding to (A-1b) out of a total of 100 parts by weight of (A-1). The proportion of (A-1b) may be within a range between any two points selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, and 20 parts by weight. The (A-1) first alkyl (meth)acrylate may be only (A-1a) and (A-1b), or may further contain other alkyl (meth)acrylates.
[0033] The first copolymerizable monomer (A-2) is at least one type of copolymerizable monomer having a functional group capable of reacting with the first crosslinking agent (A-3). The first copolymerizable monomer (A-2) is preferably at least one type selected from the group consisting of copolymerizable monomers containing a hydroxyl group and copolymerizable monomers containing a carboxyl group.
[0034] The (A-2) first copolymerizable monomer is preferably a copolymerizable monomer containing a hydroxyl group (monomer not containing a carboxyl group), for example, a hydroxyl group-containing (meth)acrylate such as a hydroxyalkyl (meth)acrylate, etc. Specific examples include at least one selected from 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxyethyl methacrylate.
[0035] The ratio of the first copolymerizable monomer (A-2) is preferably 1.0 to 20.0 parts by weight relative to 100 parts by weight of the total of (A-1). The ratio of the first copolymerizable monomer (A-2) may be within a range including any two parts by weight selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, and 20 parts by weight.
[0036] The method for producing the first (meth)acrylic polymer (A) is not particularly limited, and any known polymerization method such as solution polymerization or emulsion polymerization can be used. The weight-average molecular weight of (A) is preferably more than 100,000 and 1,000,000 or less, more preferably a copolymer of more than 100,000 and 950,000 or less, and particularly preferably more than 100,000 and 900,000 or less. If the weight-average molecular weight of (A) is 100,000 or less, even if the first (meth)acrylic resin composition is crosslinked, it is difficult to obtain a first resin layer 11 having excellent physical properties. If the weight-average molecular weight of (A) is more than 1,000,000, the solution becomes highly viscous, and the workability of the film formation process is poor.
[0037] The first (meth)acrylic resin composition used in the first resin layer 11 contains a rubber compound. The proportion of the rubber compound is 1.0 to 25.0 parts by weight with respect to 100 parts by weight of the total of (A-1). The proportion of the rubber compound may be within a range between any two points selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, and 25 parts by weight.
[0038] The rubber compound is not particularly limited as long as it is a polymer exhibiting rubber-like elasticity, but a rubber compound having excellent dispersibility or miscibility with the (meth)acrylic polymer is preferable. For example, a rubber compound made of a vinyl polymer such as an olefin elastomer, a styrene elastomer, an acrylic elastomer, an acrylic rubber, a nitrile rubber, a butadiene rubber, a polyisoprene rubber, or a natural rubber is preferable.
[0039] The rubber compound is preferably a core-shell particle formed of a rubber layer of a core portion and an acrylic layer of a shell portion. A specific example of the rubber compound is a core-shell particle formed of a rubber layer mainly made of styrene-butadiene rubber (SBR) or butadiene in the core portion and an acrylic layer mainly made of methyl methacrylate in the shell portion. The volume-based average particle size of the core-shell particle is preferably 0.1 to 0.3 μm.
[0040] The (A-3) first crosslinking agent may be a compound having a crosslinkable functional group capable of undergoing a crosslinking reaction with the functional group of the (A) first (meth)acrylic polymer. Specific examples of (A-3) include one or more compounds selected from the group consisting of epoxy compounds, aziridine compounds, and isocyanate compounds. The proportion of (A-3) first crosslinking agent is preferably 0.1 to 5 parts by weight based on 100 parts by weight of the total of (A-1).
[0041] The crosslinking agent made of an epoxy compound (epoxy-based crosslinking agent) is not particularly limited as long as it is a bifunctional or higher epoxy compound, and examples thereof include at least one selected from the group consisting of polyglycidyl ethers of polyols (including diols, glycols, and bisphenols), diglycidyl esters of dicarboxylic acids, diglycidyl-substituted amines, and tetraglycidyl-substituted diamines.
[0042] The crosslinking agent (aziridine crosslinking agent) made of an aziridine compound is not particularly limited as long as it is a bifunctional or higher aziridine compound, a compound having two or more aziridine functional groups in one molecule, etc. Examples of the aziridine functional group include a 1-aziridinyl group [-N(CH2)2], a 2-aziridinyl group, and a substituted aziridinyl group having a substituent such as a methyl group.
[0043] Examples of crosslinking agents consisting of an isocyanate compound (isocyanate-based crosslinking agents) include bifunctional isocyanates (diisocyanate compounds) such as aliphatic diisocyanates and aromatic diisocyanates, and trifunctional or higher polyisocyanate compounds such as biuret modified products, isocyanurate modified products, and adducts thereof.
[0044] The (A-4) first antioxidant is not particularly limited and can be appropriately selected from known antioxidants. Specific examples of (A-4) include at least one selected from phenol-based antioxidants, thioether-based antioxidants, phosphite-based antioxidants, and hindered amine-based antioxidants. The ratio of (A-4) first antioxidant is preferably 0.01 to 0.5 parts by weight relative to 100 parts by weight of the total of (A-1).
[0045] The first (meth)acrylic resin composition may be appropriately blended with known additives such as surfactants, curing accelerators, curing retarders, plasticizers, fillers, lubricants, processing aids, antioxidants, heat stabilizers, light stabilizers, antistatic agents, colorants, ultraviolet absorbers, infrared absorbers, etc. These additives may be used alone or in combination of two or more.
[0046] <Second (meth)acrylic resin composition> The second (meth)acrylic resin composition is used to form the second resin layer 12. (B-3) the second crosslinking agent is a difunctional or higher isocyanate compound, and is contained in an amount of 1 to 5 parts by weight per 100 parts by weight of the total of (B-1) the second alkyl (meth)acrylate.
[0047] (B) The second (meth)acrylic polymer comprises (B-1) a second alkyl (meth)acrylate, which is a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, copolymerized with 80 parts by weight or more of methyl methacrylate and 100 parts by weight of a total of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or less and the alkyl group has a carbon number of C2 to C18, and (B-2) a second copolymerizable monomer, which is a total of 5 to 30 parts by weight of at least one copolymerizable monomer that does not contain a carboxyl group and contains a hydroxyl group.
[0048] The second (meth)acrylic polymer (B) is a copolymer obtained by copolymerizing the second alkyl (meth)acrylate (B-1) and the second copolymerizable monomer (B-2). The second (meth)acrylic polymer (B) may be a copolymer consisting of only the second alkyl (meth)acrylate (B-1) and the second copolymerizable monomer (B-2), or may be a copolymer further containing other monomers.
[0049] The alkyl group of the second alkyl (meth)acrylate (B-1) may be either acyclic (straight-chain or branched) or cyclic. In the following description, the total of 100 parts by weight of the second alkyl (meth)acrylate (B-1) may be referred to as "100 parts by weight of (B-1) in total."
[0050] The (B-1) second alkyl (meth)acrylate contains (B-1a) methyl methacrylate in a ratio of 80 parts by weight or more out of a total of 100 parts by weight of (B-1). The ratio of (B-1a) may be within a range between any two points selected from 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, and 99 parts by weight.
[0051] The second alkyl (meth)acrylate (B-1) contains, in addition to methyl methacrylate (B-1a), at least one alkyl (meth)acrylate other than the above-mentioned (B-1a), (B-1b) having a homopolymer Tg of 0°C or lower and an alkyl group having a carbon number of C2 to C18.
[0052] Specific examples of (B-1b) include one or more compounds selected from the group consisting of ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, isohexyl acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and the like.
[0053] The (B-1) second alkyl (meth)acrylate contains 20 parts by weight or less of a monomer corresponding to (B-1b) out of a total of 100 parts by weight of (B-1). The proportion of (B-1b) may be in a range between any two points selected from 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, and 20 parts by weight. The (B-1) second alkyl (meth)acrylate may be only (B-1a) and (B-1b), or may further contain other alkyl (meth)acrylates.
[0054] The second copolymerizable monomer (B-2) is a copolymerizable monomer that does not contain a carboxyl group and contains a hydroxyl group, and examples thereof include hydroxyl group-containing (meth)acrylates such as hydroxyalkyl (meth)acrylates, etc. Specific examples include at least one selected from the group consisting of 8-hydroxyoctyl acrylate, 6-hydroxyhexyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxyethyl acrylate.
[0055] The ratio of the second copolymerizable monomer (B-2) is preferably 5 to 30 parts by weight relative to 100 parts by weight of the total of (B-1). The ratio of the second copolymerizable monomer (B-2) is in the range between any two points selected from 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, and 30 parts by weight.
[0056] The method for producing the second (meth)acrylic polymer (B) is not particularly limited, and any known polymerization method such as solution polymerization or emulsion polymerization can be used. The weight-average molecular weight of (B) is preferably more than 100,000 and 1,000,000 or less, more preferably a copolymer of more than 100,000 and 950,000 or less, and particularly preferably more than 100,000 and 900,000 or less. If the weight-average molecular weight of (B) is 100,000 or less, even if the second (meth)acrylic resin composition is crosslinked, it is difficult to obtain a second resin layer 12 having excellent physical properties. If the weight-average molecular weight of (B) is more than 1,000,000, the solution becomes highly viscous, and the workability of the film formation process is poor.
[0057] The second crosslinking agent (B-3) is a bifunctional or higher isocyanate compound. The second crosslinking agent (B-3) can undergo a crosslinking reaction with the hydroxyl group of the second copolymerizable monomer (B-2) contained in the second (meth)acrylic polymer (B). The proportion of the second crosslinking agent (B-3) is preferably 1 to 5 parts by weight based on 100 parts by weight of the total of (B-1).
[0058] Examples of the difunctional or higher isocyanate compound include difunctional isocyanates (diisocyanate compounds) such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), etc., and trifunctional or higher polyisocyanate compounds such as biuret modified compounds, isocyanurate modified compounds, and adducts thereof. Examples of the adducts include adducts of diisocyanate compounds and trivalent or higher polyols such as trimethylolpropane (TMP), glycerin, etc.
[0059] The bifunctional isocyanate compound may be a compound obtained by reacting a diisocyanate compound such as TDI, XDI, MDI, HDI, or IPDI with a diol compound. The diol compound may be at least one selected from the group consisting of 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol monohydroxypivalate, polyethylene glycol (PEG), and polypropylene glycol.
[0060] The second antioxidant (B-4) is not particularly limited, and can be appropriately selected from known antioxidants. Specific examples of (B-4) include at least one selected from phenol-based antioxidants, thioether-based antioxidants, phosphite-based antioxidants, and hindered amine-based antioxidants. The proportion of the second antioxidant (B-4) is preferably 0.01 to 0.5 parts by weight relative to 100 parts by weight of the total of (B-1).
[0061] The second (meth)acrylic resin composition may be appropriately blended with known additives such as surfactants, curing accelerators, curing retarders, plasticizers, fillers, lubricants, processing aids, antioxidants, heat stabilizers, light stabilizers, antistatic agents, colorants, ultraviolet absorbers, and infrared absorbers, in addition to the above-mentioned additives. These additives may be used alone or in combination of two or more. It is preferable that the second (meth)acrylic resin composition does not contain a rubber compound.
[0062] <(Meth)acrylic resin film> The (meth)acrylic resin film 10 of the embodiment has a first resin layer 11 formed by crosslinking the above-mentioned first (meth)acrylic resin composition and a second resin layer 12 formed by crosslinking a second (meth)acrylic resin composition laminated on the first resin layer 11. The second resin layer 12 serves as an adhesion improving resin layer for the first resin layer 11.
[0063] The thickness of the first resin layer 11 is preferably 10 μm or less, and more preferably 0.1 to 9 μm. The thickness of the second resin layer 12 is preferably 5 μm or less, and more preferably 0.1 to 5 μm. The second resin layer 12 may be thinner than the first resin layer 11.
[0064] The first resin layer 11 and the second resin layer 12 can be formed by using a solution casting method. Specifically, a solution of a (meth)acrylic resin composition is applied to a predetermined substrate to form a thin film, and then the thin film is dried by heating to volatilize the solvent from the thin film and crosslink the thin film. The second resin layer 12 may be laminated on the first resin layer 11, or the first resin layer 11 may be laminated on the second resin layer 12.
[0065] The substrate used in the solution casting method is not limited to a fixed flat surface, but may be a resin film unwound from a roll of resin film, a movable belt, a drum, etc. The surface property of the substrate is preferably a smooth surface, but it is also possible to transfer the unevenness to the surface of the obtained resin layer by providing the substrate with a predetermined unevenness.
[0066] The (meth)acrylic resin film 10 obtained by the solution casting method may be stretched in a predetermined direction such as the longitudinal direction or the width direction, or may be left unstretched. When it is necessary to reduce anisotropy in the use of the optical film, it is preferable to make the (meth)acrylic resin film 10 a non-stretched film. The (meth)acrylic resin film 10 may be processed into a biaxially stretched film by adding an operation of stretching the film in the longitudinal direction and the width direction. The anisotropy of the film is not limited to the anisotropy of mechanical properties such as "elongation at break" but also includes optical anisotropy such as "birefringence".
[0067] The mechanical properties of the (meth)acrylic resin film 10 depend on the application, but it is preferable that the film has a large number of folding cycles as folding resistance, a high tensile breaking strength as cutting resistance, and an appropriate breaking elongation as extensibility. For example, when the film is transported in the longitudinal direction, unwound from a roll body, or wound up onto a roll body, it is preferable that the breaking elongation is not too small so that the film can conform to the adherend, etc.
[0068] The number of folding times (JIS P8115) as the folding resistance of the (meth)acrylic resin film 10 is preferably 200 or more. Typical conditions for measuring the number of folding times include a method in which a test piece having a width of 15.0±0.1 mm and a length of about 110 mm is repeatedly folded back and forth at a speed of 175±10 times per minute under a load of 9.8 N. The number of folding times until the test piece breaks is measured.
[0069] The breaking elongation of the (meth)acrylic resin film 10 is preferably 20% or more. The breaking elongation of films can be measured in accordance with standards such as JIS K7161 (Plastics - Determination of tensile properties) and JIS K7127 (Plastics - Test method for tensile properties).
[0070] The gel fraction as a measure of the solvent resistance of the (meth)acrylic resin film 10 is preferably 90% or more. A high gel fraction can improve the solvent resistance, which is a physical property required for the (meth)acrylic resin film 10.
[0071] The (meth)acrylic resin film 10 may be used as a substrate for an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films. Examples of devices to which optical members are applied include liquid crystal panels, organic EL panels, and touch panels. When the (meth)acrylic resin film 10 is used as an optical film, it is preferably colorless and transparent.
[0072] The in-plane retardation Re of the (meth)acrylic resin film 10 is preferably 1.0 nm or less. The smaller the in-plane retardation Re, the more optically isotropic the (meth)acrylic resin film 10 becomes, and the more the change in color tone can be suppressed when the film is used for applications such as attachment to an optical device or optical inspection.
[0073] The haze value of the (meth)acrylic resin film 10 is preferably 1.0% or less. The lower the haze value, the less light is scattered when passing through the (meth)acrylic resin film 10. For example, when the (meth)acrylic resin film 10 is incorporated into an optical device such as a display, light leakage due to scattered light can be suppressed.
[0074] The (meth)acrylic resin film 10 preferably contains an antioxidant to suppress changes in appearance such as yellowing. For example, it is preferable that the (meth)acrylic resin film 10 does not change in appearance even after being stored at 70° C. for 30 days.
[0075] One or more of a hard coat layer, an antistatic layer, an antireflection layer, an antifouling layer, an antiglare layer, a low refractive index layer, an adhesive layer, a release layer, a low refractive index layer, etc. may be laminated on one or both sides of the (meth)acrylic resin film 10.
[0076] Examples of the fluorine compound used in the composition for forming the low refractive index layer include fluorine-containing copolymers which are polymers of one or more of fluorinated olefins, fluorinated vinyl ethers, fluorinated alkyl (meth)acrylates, etc., and condensates of fluorinated alkyl group-containing silane compounds, etc. The low refractive index layer may be combined with a high refractive index layer, etc. to form an antireflection layer.
[0077] The (meth)acrylic resin film 10 has excellent adhesion between the first resin layer 11 and the second resin layer 12. For example, when a cellophane tape adhesion test is performed (for details, see the test method in the Examples), the (meth)acrylic resin film 10 does not peel off from the polarizer, and only the cellophane tape peels off.
[0078] 2, the pressure-sensitive adhesive sheet of the embodiment is formed by forming a pressure-sensitive adhesive layer 21 on one or both sides of a (meth)acrylic resin film 10. The pressure-sensitive adhesive layer 21 is preferably laminated on the side of the second resin layer 12. When the pressure-sensitive adhesive layer 21 is formed on both sides of the (meth)acrylic resin film 10, the second resin layer 12 may be laminated on both sides of the first resin layer 11.
[0079] The adhesive layer 21 is preferably an adhesive layer made of a (meth)acrylic adhesive. The adhesive layer may be formed on the (meth)acrylic resin film by a known method. Specifically, known coating methods such as reverse coating, comma coating, gravure coating, slot die coating, Mayer bar coating, and air knife coating can be used.
[0080] The adhesive sheet 20 may have a release film (not shown) to protect the adhesive surface of the adhesive layer 21. The release film may be subjected to a release treatment with a silicone-based or fluorine-based release agent on the surface that comes into contact with the adhesive surface of the adhesive layer 21.
[0081] The adhesive sheet 20 may be an optical film with an adhesive layer, in which an adhesive layer 21 is laminated on at least one surface of an optical film having a base material of a (meth)acrylic resin film 10. The adhesive sheet 20 may constitute a surface protection film that is attached via the adhesive layer 21 to protect the surface of an adherend such as glass, an optical film, an optical member, or the like.
[0082] 3, the polarizing film of the embodiment is formed by forming a (meth)acrylic resin film 10 on one or both sides of a polarizer 31. The total thickness of the polarizing film 30 is preferably 80 μm or less. The polarizer 31 is not particularly limited, but may be, for example, a polyvinyl alcohol (PVA) layer containing iodine molecules (I2).
[0083] The surface treatment applied to the surface of the protective layer of the polarizer 31 may be at least one selected from the group consisting of untreated, AG treatment, LR treatment, AR treatment, AG-LR treatment, and AG-AR treatment, where AG stands for anti-glare, LR stands for low reflection, and AR stands for anti-reflection.
[0084] The (meth)acrylic resin film 10 can be used as a protective layer on at least one side of the polarizer 31. Although not particularly shown, when the (meth)acrylic resin film 10 of the embodiment is used on one side of the polarizer 31, another protective layer may be used on the opposite side. Examples of the other protective layer include acrylic resins such as triacetyl cellulose (TAC) and polymethyl methacrylate (PMMA), polyester resins such as polyethylene terephthalate (PET), cyclic olefin polymers, polycarbonate, and the like. EXAMPLES
[0085] The present invention will now be described in detail with reference to examples.
[0086] <Production of First (Meth)acrylic Resin Composition> Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, the monomers shown in (A) of Table 1 were added to the reactor so that the total of (A-1) was 100 parts by weight, and a solvent (ethyl acetate) was added. Then, 0.1 parts by weight of azobisisobutyronitrile was dropped as a polymerization initiator, and the mixture was heated to 65°C and reacted for a predetermined time to obtain a first (meth)acrylic polymer solution. The rubber compound, (A-3), and (A-4) additives shown in Table 1 were added to this solution and stirred and mixed to obtain a first (meth)acrylic resin composition.
[0087] The weight average molecular weight (Mw) of (A) was measured at the stage of the first (meth)acrylic polymer solution. In Comparative Example 10, a commercially available PMMA film (thickness: 80 μm) produced by melt extrusion was used, and the film was dissolved in methyl ethyl ketone (MEK) solvent to measure the Mw of the polymer.
[0088] [Table 1]
[0089] The meanings of the abbreviations (compound names, etc.) used in Table 1 are as follows: The numerical values following these abbreviations in Table 1 indicate parts by weight relative to a total of 100 parts by weight of (A-1).
[0090] As (A-1), methyl methacrylate (MMA), methyl acrylate (MA), n-butyl methacrylate (BMA), ethyl methacrylate (EMA), t-butyl acrylate (TBA), and isobutyl methacrylate (IBMA) were used. As (A-2), 8-hydroxyoctyl methacrylate (8HOMA), 6-hydroxyhexyl methacrylate (6HHMA), 4-hydroxybutyl methacrylate (4HBMA), 2-hydroxyethyl methacrylate (HEMA), acrylic acid (Aac), 8-hydroxyoctyl acrylate (8HOA), and 6-hydroxyhexyl acrylate (6HHA) were used.
[0091] As rubber compounds (particle diameter is volume-based average particle diameter), "M-230" is Kane Ace (registered trademark) M-230 (core-shell particle, particle diameter: 0.1 μm, core part: SBR, shell part: MMA, product name of Kaneka Corporation), "M-210" is Kane Ace (registered trademark) M-210 (core-shell particle, particle diameter: 0.2 μm, core part: SBR, shell part: MMA, product name of Kaneka Corporation), "B-513" is Kane Ace (registered trademark) B-513 (core-shell particle, particle diameter: 0.2 μm, core part: butadiene, shell part: MMA, product name of Kaneka Corporation), and "LP-4100" is Metablen (registered trademark) LP-4100 (acrylic rubber particle, particle diameter: 1 μm, product name of Mitsubishi Chemical Corporation).
[0092] As for (A-3), "HX" is Coronate (registered trademark) HX (HDI isocyanurate, trade name of Tosoh Corporation), "HL" is Coronate (registered trademark) HL (HDI adduct, trade name of Tosoh Corporation), "140N" is Takenate (registered trademark) D-140N (IPDI adduct, trade name of Mitsui Chemicals, Inc.), and "TX" is TETRAD (registered trademark)-X (tetrafunctional epoxy compound, trade name of Mitsubishi Gas Chemical Company, Inc.).
[0093] As for (A-4), "C-1" is Irganox (registered trademark) 1010 (phenol-based antioxidant, BASF's trade name), "C-2" is Tinuvin (registered trademark) 292 (hindered amine-based antioxidant, BASF's trade name), "C-3" is Irgafos (registered trademark) 168 (phosphite-based antioxidant, BASF's trade name), and "C-4" is Irganox (registered trademark) PS802FL (thioether-based antioxidant, BASF's trade name).
[0094] <Production of second (meth)acrylic resin composition> Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, the monomers shown in (B) of Table 2 were added to the reactor so that the total of (B-1) was 100 parts by weight, and a solvent (ethyl acetate) was added. Then, 0.1 parts by weight of azobisisobutyronitrile was dropped as a polymerization initiator, and the mixture was heated to 65°C and reacted for a predetermined time to obtain a second (meth)acrylic polymer solution. The rubber compound, (B-3), and (B-4) shown in Table 2 were added to this solution, and the additives were stirred and mixed to obtain a second (meth)acrylic resin composition.
[0095] The weight average molecular weight (Mw) of (B) was measured at the stage of the second (meth)acrylic polymer solution. In Comparative Examples 1 and 9, the second resin layer was not laminated.
[0096] [Table 2]
[0097] The meanings of the abbreviations (compound names, etc.) used in Table 2 are as follows: The numerical values following these abbreviations in Table 2 indicate parts by weight relative to a total of 100 parts by weight of (B-1).
[0098] As (B-1), methyl methacrylate (MMA), 2-ethylhexyl acrylate (2EHA), n-butyl acrylate (BA), ethyl acrylate (EA), isooctyl acrylate (IOA), and methyl acrylate (MA) were used. As (B-2), 8-hydroxyoctyl acrylate (8HOA), 6-hydroxyhexyl acrylate (6HHA), 4-hydroxybutyl acrylate (4HBA), 2-hydroxyethyl acrylate (HEA), acrylic acid (Aac), and 2-hydroxyethyl methacrylate (2HEMA) were used.
[0099] The rubber compounds and (B-4) in Table 2 use the same abbreviations as the rubber compounds and (A-4) in Table 1. The abbreviations for "HX", "HL", and "TX" in (B-3) are the same as those in Table 1. "TPA-100" is Duranate (registered trademark) TPA-100 (HDI isocyanurate, a trade name of Asahi Kasei Corporation). "B-3-1" is a bifunctional isocyanate compound obtained by reacting HDI with 2,2-dimethyl-1,3-propanediol monohydroxypivalate. "B-3-2" is a bifunctional isocyanate compound obtained by reacting HDI with 1,6-hexanediol.
[0100] <Preparation of (meth)acrylic resin film> In Examples 1 to 5 and Comparative Examples 1 to 9, the (meth)acrylic resin compositions shown in Tables 1 and 2 were formed into resin films by solution casting, and the films were heated and dried under temperature conditions suitable for drying the solvent and curing the crosslinking agent, and crosslinked to form laminates. The thickness of the first resin layer is shown in Table 1, and the thickness of the second resin layer is shown in Table 2. In Comparative Example 10, the above-mentioned commercially available PMMA film was used. In the following explanation of the test methods, the (meth)acrylic resin films of the Examples or Comparative Examples are referred to as test films.
[0101] <Adhesion test> The surface of the test film to be attached to the polarizer was subjected to corona treatment (0.15 kW, 3 m / min), and the film was bonded to the PVA layer of the polarizing plate via a PVA adhesive. The polarizing plate has a 30 μm PVA layer on the polarizer and a 30 μm TAC layer on the opposite substrate. A compound made by Mitsubishi Chemical (100 parts of Gohsenex (registered trademark) Z-200 and 10 parts of Safelink (registered trademark) SPM-01) was applied as the PVA adhesive.
[0102] The test film was laminated to a polarizing plate, dried at 80°C for 5 minutes, removed from the oven, and left at 23°C for 1 hour, after which cellophane tape was laminated to the surface of the test film. The cellophane tape was peeled off in the 180° direction at a speed of 300 mm / min, and the condition of the test film was judged visually.
[0103] The adhesion was evaluated as "○" when only the cellophane tape peeled off, "△" when the test film remained in fragments on the peeled cellophane tape, and "×" when the test film remained over the entire surface of the peeled cellophane tape and peeled off together with the cellophane tape.
[0104] <Total thickness of polarizing plate> A polarizing plate was prepared by using the test film as the surface substrate on one side, a polarizer having a PVA layer of 30 μm and a substrate on the opposite side having a TAC layer of 30 μm, and the total thickness of the polarizing plate was measured.
[0105] <Haze value> The total haze value of the test film was measured using a haze meter (Murakami Color Laboratory Co., Ltd., model: HM-150N) in accordance with JIS K7136 (2000).
[0106] <Appearance Change> A test piece made from the test film was left at 70°C for 30 days, and then the change in appearance of the test piece was visually judged. The appearance of the test piece was compared with that of the test film before the 70°C x 30-day storage (or the test film that was left at 23°C for the same period and was assumed to have no change in appearance), and the test piece was rated as "○" if there was no change in appearance at all, "△" if there was a partial change in color in the appearance, and "×" if there was a change in appearance and yellowing.
[0107] <Bending resistance> Using a test piece prepared from the test film, the number of times the test piece could be folded back and forth until it broke (fold endurance) was measured in accordance with JIS P8115.
[0108] <Solvent resistance> The mass of a test piece made from the test film was accurately measured, and it was immersed in methyl ethyl ketone (MEK) for 24 hours, and then filtered through a 200-mesh wire screen. The filtered material was dried at 100°C for 1 hour, and the mass of the insoluble matter (residue) obtained was accurately measured to measure the gel fraction (%). Gel fraction (%) = mass of insoluble matter (g) / mass of test piece (g) × 100
[0109] <Tensile strength and elongation> A shear tensile test was carried out using a test piece prepared from the test film, and the tensile breaking strength (MPa) and elongation (%) were determined.
[0110] <Phase difference Re> Using the test pieces prepared from the test films, the in-plane retardation (Re) values (nm) were measured with a retardation measuring device.
[0111] [Table 3]
[0112] As shown in Table 3, the (meth)acrylic resin films of Examples 1 to 5 were excellent in folding resistance, cut resistance, elongation, and solvent resistance, and were able to improve adhesion to adherends while maintaining optical properties. The (meth)acrylic resin films of Comparative Examples 1 to 10 were inferior in any one of folding resistance, cut resistance, elongation, solvent resistance, optical properties, and adhesion to adherends. [Explanation of symbols]
[0113] 10: (meth)acrylic resin film, 11: first resin layer, 12: second resin layer, 20: adhesive sheet, 21: adhesive layer, 30: polarizing film, 31: polarizer.
Claims
1. a first resin layer obtained by crosslinking a first (meth)acrylic resin composition containing (A) a first (meth)acrylic polymer, a rubber compound, (A-3) a first crosslinking agent, and (A-4) a first antioxidant; A (meth)acrylic resin film laminated with a second resin layer which is an adhesion improving resin layer for the first resin layer and is obtained by crosslinking a second (meth)acrylic resin composition containing (B) a second (meth)acrylic polymer, (B-3) a second crosslinking agent, and (B-4) a second antioxidant, The first (meth)acrylic polymer (A) is (A-1) a first alkyl (meth)acrylate, comprising 80 parts by weight or more of methyl methacrylate and 100 parts by weight of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0° C. or more and the alkyl group has a carbon number of C1 to C14; (A-2) a first copolymerizable monomer, which is a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, obtained by copolymerizing a total of 1.0 to 20.0 parts by weight of at least one or more copolymerizable monomers having a functional group capable of reacting with the (A-3) first crosslinking agent; The rubber compound is present in an amount of 1.0 to 25.0 parts by weight based on 100 parts by weight of the first alkyl (meth)acrylate (A-1), The second (meth)acrylic polymer (B) is (B-1) a second alkyl (meth)acrylate, comprising 80 parts by weight or more of methyl methacrylate and 100 parts by weight of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0° C. or less and the alkyl group has a carbon number of C2 to C18; (B-2) a second copolymerizable monomer, which is a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000 obtained by copolymerizing a total of 5 to 30 parts by weight of at least one copolymerizable monomer that does not contain a carboxyl group and contains a hydroxyl group, The second crosslinking agent (B-3) is a difunctional or higher isocyanate compound, the (B-3) second crosslinking agent is in a ratio of 1 to 5 parts by weight based on 100 parts by weight in total of the (B-1) second alkyl (meth)acrylate, a thickness of the first resin layer being 10 μm or less, a thickness of the second resin layer being 5 μm or less, and a haze value of the (meth)acrylic resin film being 1.0% or less.
2. the (A-2) first copolymerizable monomer is at least one monomer selected from the group of monomers consisting of copolymerizable monomers containing a hydroxyl group and copolymerizable monomers containing a carboxyl group, the (A-3) first crosslinking agent is at least one selected from the group consisting of epoxy compounds, aziridine compounds, and isocyanate compounds; the (A-3) first crosslinking agent is present in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the (A-1) first alkyl (meth)acrylate in total; the (A-4) first antioxidant is at least one selected from a phenol-based antioxidant, a thioether-based antioxidant, a phosphite-based antioxidant, and a hindered amine-based antioxidant; The (meth)acrylic resin film according to claim 1, characterized in that the (A-4) first antioxidant is present in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the (A-1) first alkyl (meth)acrylate in total.
3. the rubber compound is a core-shell particle formed of a rubber layer mainly made of SBR or butadiene in the core portion and an acrylic layer mainly made of methyl methacrylate in the shell portion, 2. The (meth)acrylic resin film according to claim 1, wherein the core-shell particles have a volume-based average particle size of 0.1 to 0.3 μm.
4. The (meth)acrylic resin film according to claim 1, wherein the (A-2) first copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group, and is at least one selected from the group consisting of 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxyethyl methacrylate.
5. the second antioxidant (B-4) is at least one selected from a phenol-based antioxidant, a thioether-based antioxidant, a phosphite-based antioxidant, and a hindered amine-based antioxidant; The (meth)acrylic resin film according to claim 1, characterized in that the (B-4) second antioxidant is contained in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the (B-1) second alkyl (meth)acrylate in total.
6. The (meth)acrylic resin film according to claim 1, wherein the (B-2) second copolymerizable monomer is a copolymerizable monomer containing a hydroxyl group, and is at least one selected from the group consisting of 8-hydroxyoctyl acrylate, 6-hydroxyhexyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxyethyl acrylate.
7. 2. The (meth)acrylic resin film according to claim 1, wherein the first resin layer has a thickness of 0.1 to 9 μm, and the second resin layer has a thickness of 0.1 to 5 μm.
8. The (meth)acrylic resin film according to claim 1, wherein the (meth)acrylic resin film has an in-plane retardation Re of 1.0 nm or less.
9. 2. The (meth)acrylic resin film according to claim 1, wherein the (meth)acrylic resin film has a gel fraction of 90% or more as a solvent resistance, a folding endurance count (JIS P8115) of 200 or more as a folding endurance, and a breaking elongation of 20% or more as a folding endurance.
10. 2. The (meth)acrylic resin film according to claim 1, wherein in a cellophane tape adhesion test in which the (meth)acrylic resin film is attached to one surface of a polarizer with a PVA adhesive, and then cellophane tape is attached to a surface of the (meth)acrylic resin film and then peeled off, the (meth)acrylic resin film does not peel off and only the cellophane tape peels off.
11. A pressure-sensitive adhesive sheet comprising the (meth)acrylic resin film according to any one of claims 1 to 10 and a pressure-sensitive adhesive layer formed on one or both sides of the (meth)acrylic resin film.
12. A polarizing film comprising the (meth)acrylic resin film according to any one of claims 1 to 10 formed on one or both sides of a polarizer, the polarizing film having a total thickness of 80 µm or less.
Citation Information
Patent Citations
Acrylic resin film composition and molded article using the same
JP2009286960A
Acrylic resin composition, and molded product and film made from same
WO2016139927A1